Association Between ABCA1 Gene Polymorphisms and the Risk of Hypertension in the Chinese Han Population - Ren, Yanli; Tong, Enyu; Di, Chunhong; Zhang, Yunheng; Xu, Liangwen; Tan, Xiaohua; Yang, Lei (Frontiers in Public Health, 2022)
Background: Hypertension is rising as a major public health burden around the world. This study explored the association of single-nucleotide polymorphisms (SNPs) in the ATP Binding Cassette Subfamily A1 (ABCA1) gene and hypertension among Chinese Han adults. Method: A total of 2296 Han Chinese in southeast China were recruited for this study. We collected medical reports, lifestyle details, and blood samples from individuals. The polymerase chain reaction-ligase detection reaction (PCR-LDR) method was used to detect the genotypes of these SNPs in the ABCA1 gene. Results: After adjusting some covariates, the additive and recessive models of the rs2472510 and rs2515614 were significantly associated with hypertension. The haplotypes TCTA (rs2297406-rs2472433-rs2472510-rs2515614.) were associated with high SBP, and the haplotype CCTA, TCTA and TTTA were associated with high DBP. Conclusion: The results of the relationship between the polymorphisms of rs2297406, rs2472433, rs2472510 and rs2515614 in ABCA1 and hypertension in southeastern China would provide a theoretical basis for genetic screening and disease prevention.